2010
DOI: 10.1186/1471-2156-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiling of candidate genes in testis of pigs exhibiting large differences in androstenone levels

Abstract: BackgroundBoar taint is an unpleasant odor and flavor of the meat and occurs in a high proportion of uncastrated male pigs. Androstenone, a steroid produced in testis and acting as a sex pheromone regulating reproductive function in female pigs, is one of the main compounds responsible for boar taint. The primary goal of the present investigation was to determine the differential gene expression of selected candidate genes related to levels of androstenone in pigs.ResultsAltogether 2560 boars from the Norwegia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 62 publications
5
36
1
Order By: Relevance
“…These results were consistent with those of Grindflek's et. al (2010) study about Duroc and Landrace (Grindflek et al, 2010). In a similar study in 108 kg live weight, the level of plasma testosterone was 75.1 nM in wild pigs and 58.5 nM in Yorkshire pigs (Babol et al, 1999), which are greater than those of Bama pigs (7.13 ng/mL plasma testosterone at 12 months of age) in this study.…”
Section: Relative Boar Taint-gene Expression In the Testicles Of Bamasupporting
confidence: 93%
See 1 more Smart Citation
“…These results were consistent with those of Grindflek's et. al (2010) study about Duroc and Landrace (Grindflek et al, 2010). In a similar study in 108 kg live weight, the level of plasma testosterone was 75.1 nM in wild pigs and 58.5 nM in Yorkshire pigs (Babol et al, 1999), which are greater than those of Bama pigs (7.13 ng/mL plasma testosterone at 12 months of age) in this study.…”
Section: Relative Boar Taint-gene Expression In the Testicles Of Bamasupporting
confidence: 93%
“…StAR has a key effect on limiting the rate of cholesterol metabolism and steroid hormone synthesis. As steroid hormone, StAR promotes the transitioning of cholesterol from the outer to the inner mitochondrial membrane as an in vivo steroidal substance (Ning et al, 2009a;Ning et al, 2009b), and StAR has an obvious positive correlation with androstenone phenotype (Grindflek et al, 2010). The effects of several transcription factor on the expression levels of several transcripts of the metabolism of androstenone and skatole have been tested (Gray and Squires, 2013a;Gray and Squires, 2013b), except for COUP-TF1.…”
Section: Introductionmentioning
confidence: 99%
“…ESR1 is located on SSC1p24-25 which is evidence of harbouring several QTL for sperm count and sperm motility (Ren et al, 2009). ESR1 is reported to be a promising candidate gene for boar sperm quality and fertility (Gunawan et al, 2011) and is genetically related to androstenone (Grindflek et al, 2010). To our knowledge, this is the first association study of ESR1 polymorphism with boar taint compounds.…”
Section: Discussionmentioning
confidence: 81%
“…3) seemed to be consistent with the results of mRNA expression. The CYP21 mRNA is reported to be down regulated in Norwegian Landrace boars with a high androstenone level (Grindflek, Berget, Moe, Oeth, & Lien, 2010). CYP21 is a member of the cytochrome P450 superfamily enzyme, a key enzyme for corticosteroid-ogenesis (Deslandes et al, 2001;Payne & Youngblood, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…There were numerous attempts to identify genetic markers which would allow the selection of free of taint pigs (Duijvesteijn et al, 2010;Gregersen et al, 2012;Gunawan et al, 2013a and2013b). Recently, it was shown that 12 candidate genes in testes of boars with high and low androstenone levels were differentially expressed (Grindflek et al, 2010).…”
Section: Introductionmentioning
confidence: 99%